The history of pain measurement in humans and animals - Mogil, Jeffrey S. (Frontiers in Pain Research, 2022)
Pain needs to be measured in order to be studied and managed. Pain measurement strategies in both humans and non-human animals have varied widely over the years and continue to evolve. This review describes the historical development of human and animal algesiometry.